Keseimbangan dalam Produksi, Distribusi dan Konsumsi sebagai Upaya Pembangunan Ekonomi Berkelanjutan - Ihwanudin , Nandang; Saripudin , Udin; Suryani , Suryani (Al-Insyiroh: Jurnal Studi Keislaman, 2020)
This research is motivated by human behavior in meeting their needs. They meet consumption needs by making production efforts at their own capacity while they have the ability to do so. If unable to do so, then the fulfillment of these needs is met through distribution from the production of other parties. In an effort to meet their needs or even desires, humans often do it beyond their proper limits. They do this by violating the integrity and harmony between producers, consumers, and distributors. Even often in the efforts of economic activities, disrupting the stability and sustainability of ecosystems. This study aims to formulate the concept of balance in production, distribution and consumption as an effort to sustainable economic development. The method used is descriptive analysis method with documentation study. The results of the study found that sustainable economic development can be achieved through a balance of economic actors in the production, distribution and consumption sectors.